Apolipoprotein E gene polymorphisms and intraventricular haemorrhage in infants born preterm: a large prospective multicentre cohort study. (7th August 2018) - Dzietko, Mark; Schulz, Soeren; Preuss, Michael; Haertel, Christoph; Stein, Anja; Felderhoff‐Mueser, Ursula; Goepel, Wolfgang
Abstract : Aim: Infants born preterm are at risk of intraventricular haemorrhage (IVH) but individual susceptibility related to genes is not well defined in this vulnerable population. Apolipoprotein genotypes APOE2 and APOE4 increase the hazard of cerebral haemorrhages in adults. We investigated whether APOE is associated with prevalence of IVH and is likely to have a particular genotype. Method: In this prospective study, 5075 infants born preterm with genotype APOE3 were compared to 965 ( APOE2 ) and 1912 ( APOE4 ) individuals, to analyse the association between APOE genotype and grade III and IV IVH. We used a logistic regression model including gestational age, antenatal steroid treatment, 5‐minute Apgar scores less than 3, intubation, pneumothorax, small for gestational age, multiple birth, sex, and maternal descent as independent factors. Results: The APOE2 (20.1%) and APOE4 (19.8%) genotypes were significantly more prevalent in infants with IVH than in those with the APOE3 haplotype (17.4%) ( APOE2 : odds ratio [OR] 1.33, 95% confidence interval [CI] 1.00–1.76; APOE4 : OR 1.39, 95% CI 1.12–1.74). Infants with two polymorphisms had the highest risk of IVH (8.7%; OR 1.63, 95% CI 1.09–2.45). Interpretation: APOE2 and APOE4 genotypes are relevant risk factors for IVH in infants born preterm. Our findings improve our understanding of the genetic contributions to IVH. What this paper adds: In infants born preterm, APOE2 and APOE4 genotypes are associated with intraventricular haemorrhage (IVH). Two harmful gene copies further increase the risk of IVH. APOE2 genotypes were at highest risk for severe IVH. This article is commented on by Vollmer on page287 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.